THE EFFECTIVENESS OF SIMULATORS FOR UNMANNED AERIAL VEHICLES - Saitaxmadov Maqsud (International Journal of Artificial Intelligence for Digital Marketing, 2024)
Unmanned aerial vehicles (UAVs), commonly known as drones, have become widespread in various sectors including the military, agriculture, logistics and entertainment. Operator training and real-world testing of UAV systems can be costly, time-consuming, and risky. Simulations offer a viable solution by providing a controlled, cost-effective and safe environment for learning and development. This article examines the effectiveness of UAV simulators, delving into their benefits, their underlying mathematical models, and their applications in training, development, and operational efficiency